ANDROID BASED VEHICLE WASH BOOKING SYSTEM DESIGN (Case Study: Labuhan Car Wash) - Fernando Mexco; April Zahmi; Gustri Efendi; Januardi Nasir (Journal of Scientech Research and Development, 2024)
Motor vehicle washing is a service industry that is in demand, especially in big cities, because of the high number of vehicles owned by people. Data from the Central Statistics Agency (BPS) in 2020 shows that Indonesia has 136,320,000 motorized vehicles, including motorbikes, passenger cars, trucks and buses. One of the providers of motor vehicle washing services in Padang City is Labuhan Car Wash, which offers various washing packages with various facilities. However, Labuhan Car Wash faces challenges in the ordering process due to inefficiency and ineffectiveness. In this modern era, information technology such as Android-based cell phone systems play an important role in streamlining processes and saving time. Therefore, an efficient system is needed to facilitate the process of ordering a vehicle wash. One solution is the development of an Android-based vehicle wash ordering system which not only makes it easier for customers to order and pay for vehicle wash services, but also helps business owners manage their business data and information. By implementing this system, it is hoped that it can increase the efficiency and effectiveness of the vehicle wash ordering process at Labuhan Car Wash.